2020
DOI: 10.3390/antib9040064
|View full text |Cite
|
Sign up to set email alerts
|

Fc-Engineering for Modulated Effector Functions—Improving Antibodies for Cancer Treatment

Abstract: The majority of monoclonal antibody (mAb) therapeutics possess the ability to engage innate immune effectors through interactions mediated by their fragment crystallizable (Fc) domain. By delivering Fc-Fc gamma receptor (FcγR) and Fc-C1q interactions, mAb are able to link exquisite specificity to powerful cellular and complement-mediated effector functions. Fc interactions can also facilitate enhanced target clustering to evoke potent receptor signaling. These observations have driven decades-long research to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 176 publications
(309 reference statements)
2
104
0
Order By: Relevance
“…CDC, an effector function of IgG (and IgM) antibodies, is a cytolytic cascade triggered by binding of the complement C1q to the constant region of cell-bound antibodies followed by activation of a series of complement proteins [ 19 , 20 ]. Our results showed that, while the anti-hTfR mAb used in pabinafusp alfa elicited CDC, the fusion protein did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CDC, an effector function of IgG (and IgM) antibodies, is a cytolytic cascade triggered by binding of the complement C1q to the constant region of cell-bound antibodies followed by activation of a series of complement proteins [ 19 , 20 ]. Our results showed that, while the anti-hTfR mAb used in pabinafusp alfa elicited CDC, the fusion protein did not.…”
Section: Discussionmentioning
confidence: 99%
“…ADCC, another effector function of IgG antibodies, is the process of killing opsonized cells (cells coated with antibodies) by effector cells of the immune system, such as natural killer cells [ 19 , 20 ]. Thus, ADCC requires an interaction between the antibody CDR domains and the antigens on target cells as well as binding of the antibody Fc domains to Fcγ receptors on effector cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, changing the amino acid sequence, exemplified by S239D/I332E (SDIE) in 293C3-SDIE, represents another option. Interestingly, the SDIE-modified CD19 antibody Tafasitamab was recently FDA-approved for the treatment of r/r diffuse large B cell lymphoma (DLBCL), and several other Fc-optimized antibodies carrying the SDIE modification are currently being evaluated in clinical trials [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that IgG antibodies coating on pathogens can evoke the immune effector functions such as antibody dependent cell-mediated cytotoxicity (ADCC), antibody induced complement dependent cytotoxicity (CDC), and antibody dependent cell-mediated phagocytosis (ADCP) [ 12 , 13 ]. While CDC is mediated and initiated by the binding of Fc domain to the first component of complement, C1q [ 14 ], ADCC and ADCP are executed by the innate immune cells such as natural killer cells and macrophages.…”
Section: Antibody Efficacy Improvementmentioning
confidence: 99%